Asset prices and central bank policy - Cecchetti, Stephen G. (Stephen Giovanni); International Center for Monetary and Banking Studies .; Centre for Economic Policy Research (Great Britain) (Geneva : International Center for Monetary and Banking Studies, 2000)
This text is the second report in a series of "Geneva Reports on the World Economy", organized by the Center for International Monetary and Banking Studies, Geneva. The report focuses on asset price inflation and discusses what can be done to alleviate this growing problem.
Includes bibliographical references (p. 135-140).
Keywords: Monetary policy; Inflation (Finance) -- Forecasting; Securities -- Prices; Assets (Accounting) -- Prices